FACTORS ASSOCIATED WITH THE REPRESENTATIVENESS OF THE TRANSFORMATION ZONE IN CYTOPATHOLOGICAL CERVICAL TESTS - Vanessa Aparecida Gasparin; Érica de Brito Pitilin; Rafaela Bedin; Fernanda Karla Metelski; Daniela Savi Geremia; Claudio Claudino da Silva Filho (Universidade Federal do Paraná, 2016)
The objective was to analyze the factors associated with the representativeness of the Transformation Zone in cervical screening tests. A retrospective and quantitative study was undertaken through the analyses of the cytopathology tests registered in the Cancer Information System in 2014. The final sample resulted in 1,157 reports. For the data analysis, the software Statistical Package for the Social Sciences was used. Of all tests,96.88% were undertaken for disease control and screening and 24.3% did not present the transformation zone. The factors that influenced the representativeness of the transformation zone were age between 25 and 64 years, use of oral contraception, hormone replacement therapy and metaplastic epithelium. These factors can be considered facilitators to capture a satisfactory sample with the possible reduction of false-negative results, which would entail a delay for the early treatment of cervical cancer.